New numerical approaches for modeling thermochemical convection in a compositionally stratified fluid - Puckett, Elbridge Gerry; Turcotte, Donald L.; He, Ying; Lokavarapu, Harsha; Robey, Jonathan M.; Kellogg, Louise H. (Physics of the earth and planetary interiors, 2018)
•A comprehensive study of the role of a compositional boundary in thermal convection.•Discussion of alternative numerical methods for handling sharp compositional boundaries.•Quantitative treatment of the importance of the buoyancy ratio B on thermal convection.•Relation of compositional boundaries to large low shear velocity provinces in the earth’s mantle. Geochemical observations of mantle-derived rocks favor a nearly homogeneous upper mantle, the source of mid-ocean ridge basalts (MORB), and heterogeneous lower mantle regions. Plumes that generate ocean island basalts are thought to sample the lower mantle regions and exhibit more heterogeneity than MORB. These regions have been associated with lower mantle structures known as large low shear velocity provinces (LLSVPS) below Africa and the South Pacific. The isolation of these regions is attributed to compositional differences and density stratification that, consequently, have been the subject of computational and laboratory modeling designed to determine the parameter regime in which layering is stable and understanding how layering evolves. Mathematical models of persistent compositional interfaces in the Earth’s mantle may be inherently unstable, at least in some regions of the parameter space relevant to the mantle. Computing approximations to solutions of such problems presents severe challenges, even to state-of-the-art numerical methods. Some numerical algorithms for modeling the interface between distinct compositions smear the interface at the boundary between compositions, such as methods that add numerical diffusion or ‘artificial viscosity’ in order to stabilize the algorithm. We present two new algorithms for maintaining high-resolution and sharp computational boundaries in computations of these types of problems: a discontinuous Galerkin method with a bound preserving limiter and a Volume-of-Fluid interface tracking algorithm. We compare these new methods with two approaches widely used for modeling the advection of two distinct thermally driven compositional fields in mantle convection computations: a high-order accurate finite element advection algorithm with entropy viscosity and a particle method that carries a scalar quantity representing the location of each compositional field. All four algorithms are implemented in the open source finite element code ASPECT, which we use to compute the velocity, pressure, and temperature associated with the underlying flow field. We compare the performance of these four algorithms on three problems, including computing an approximation to the solution of an initially compositionally stratified fluid at Ra=105 with buoyancy numbers B that vary from no stratification at B=0 to stratified flow at large B.